INTEGRASI PANDANGAN OKSIDENTALISME DALAM KURIKULUM PAI: MEMBENTUK KARAKTER MUSLIM YANG BERWAWASAN GLOBAL DI SEKOLAH NEGERI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the integration of Hassan Hanafi’s concept of Occidentalism into the Islamic Religious Education (IRE) curriculum in public schools as a strategy for shaping the character of Muslims with a global perspective. The main issue raised is the hegemony of Western epistemology, which causes intellectual inferiority and an identity crisis among Muslim students, exacerbated by the unfiltered flow of digital globalization. The urgency of this study lies in the need to deconstruct the myth of Western universality in order to build intellectual sovereignty for the younger generation. The methodology employed is qualitative research using a literature review and content analysis of the Merdeka Curriculum documents and PAI materials. The findings indicate that the integration of Occidentalism through the dimension of Global Diversity within the Pancasila Student Profile Strengthening Project (P5) enables students to position themselves as critical subjects (the ego) toward Western civilization (the other). This finding indicates that adaptive religious education is capable of transforming a mentality of blind imitation into critical-transformative awareness, thereby shaping individuals who are morally resilient and competitive on the international stage.